Qualitative comparative analysis (QCA) of theories and methods for developing virtual museum: identification of the issues and problems - Rostamian, Moien; Barkeshli, Mandana (2013)
Since geographic borders and lines among the countries are losing their old rationales in a globalizing world by more and more every day usage of digital networks, there are some concerns about preserving the local cultural values or traditions of each nation, while in the other hand, digital networks can be implemented not only to preserve the cultural values and aspects but also represent these values world widely for further study by sharing the collected information regardless of place and time. In this paper, I am addressing the issues and problems in the previous efforts in the plan and theory side of developing a Virtual Museum (VM) using the Qualitative Comparative Analysis (QCA) of different previous approach toward online virtualization of cultural organizations and museums. By identifying the deficiencies, based on the further research which is under the process as my P.hD thesis, a new guide line will be provided as a model to develop Virtual Museum, more effectively and efficiently, which can play an important role in globalization, helping to preserve the classic heritage and forecasting the new cultural movements.